Predicting Factors for Mortality in Patients After the Modified Blalock-Taussig Shunt Procedure in Developing Countries: A Retrospective Study - Amelia, Putri; Advani, Najib; Pulungan, Aman; Djer, Mulyadi; Hegar, Badriul; Prawira, Yogi; Sukardi, Rubiana (International journal of general medicine, 2023)
Background: Blalock-Taussig (BT) is a palliative procedure that preserves blood circulation to the lungs and alleviates cyanosis in patients with congenital heart diseases and reduced pulmonary blood flow. BT shunt remains a routinely performed procedure in developing countries before definitive surgery. However, evidence on predictor factors of mortality after this procedure is still scarce in Indonesia. This study evaluated the predictive factors of mortality after the BT shunt procedure. Methods: This retrospective study evaluated the medical record data of all postoperative BT shunt patients at Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia, from 2016 to 2020. We performed univariate and multivariate analyses to identify the predictors of in-hospital mortality. Results: The total subjects in this study were 197 children, 107 (54.3%) boys and 90 (45.7%) girls. The median values for age and body weight at the time of surgery were 20 months (11 days - 32 years) and 7.9 (2.7-42) kg. The most prevalent diagnosis was the Tetralogy of Fallot, found in 80 (40.6%) patients. In-hospital postoperative mortality was 20.8% (41 patients). Based on multivariate analysis, predictors associated with mortality were weight <4.25 kg (OR 20.9; 95% CI 7.4-59.0; p < 0.0001) and emergency procedures (OR 3.5; 95% CI 1.3-9.5; p = 0.016). Conclusion: The mortality rate after BT shunt at PJT Rumah Sakit Cipto Mangunkusumo was 20.8%. Based on multivariate analysis, weight <4.25 kg and emergency procedures are two predictors of mortality in BT shunt. Keywords: Blalock-Taussig shunt, congenital heart disease, Indonesia, mortality